FIGO good practice recommendations on the use of prenatal corticosteroids to improve outcomes and minimize harm in babies born preterm. Issue 1 (14th September 2021) - Norman, Jane; Shennan, Andrew; Jacobsson, Bo; Stock, Sarah J.; ,
Abstract: For women with a singleton or a multiple pregnancy in situations where active neonatal care is appropriate, and for whom preterm birth is anticipated between 24 and 34 weeks of gestation, one course of prenatal corticosteroids should ideally be offered 18 to 72 h before preterm birth is expected to improve outcomes for the baby. However, if preterm birth is expected within 18 h, prenatal corticosteroids should still be administered. One course of corticosteroids includes two doses of betamethasone acetate/phosphate 12 mg IM 24 h apart, or two doses of dexamethasone phosphate 12 mg IM 24 h apart. In women in whom preterm birth is expected within 72 h and who have had one course of corticosteroids more than a week previously, one single additional course of prenatal corticosteroids could be given at risk of imminent delivery. Prenatal corticosteroids should not be offered routinely to women in whom late preterm birth between 34 and 36 weeks is anticipated. In addition, prenatal corticosteroids should not be given routinely before cesarean delivery at term. Neither should prenatal corticosteroids be given "just in case". Instead, prenatal steroid administration should be reserved for women for whom preterm birth is expected within no more than 7 days, based on the woman's symptoms or an accurate predictive test. Synopsis: Antenatal corticosteroids given to pregnant women a few days before preterm delivery under 34 weeks of gestation decrease the risk of perinatal mortality and short‐ and long‐term morbidity.